Optimization of Ready-to-Cook Chicken Cutlet Mix Using Different Levels of Antioxidant Dietary Fiber Enriched Dehydrated Vegetable Mix - Tomar, Serlene; Chauhan, Geeta; Das, Annada; Meshram, Somesh (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted during a period of six (6) months from June to December, 2019 at the Division of Livestock Products Technology, Indian Veterinary Research Institute, Izatnagar, Uttar Pradesh, India to develop a nutritious, convenience and shelf stable ready-to-cook chicken cutlet mix extended with dried vegetables as a source of antioxidant dietary fiber. Dehydrated vegetable mix was added at three different levels (2.5, 5 and 7.5%) and compared with control having no added vegetables. The results revealed that the dehydrated vegetable mix proved to be an additional source of minerals and dietary fibre in the chicken cutlet mix. Extension of ready-to-cook cutlet mix improved the yield, and colour saturation of the mix. The chicken cutlets prepared using the extended mix offered improved juiciness and overall acceptability along with better textural profile. Physico-chemical analysis revealed that the mix was shelf stable due to its low water activity and moisture content and hence could probably be stored for long periods of time. Extension of the mix with DVM enhanced the functionality of the product by improving its antioxidant potential. However, as indicated by sensory evaluation higher levels of dehydrated vegetables (7.5%) altered the colour, texture and flavour of developed product. Hence, 5% level of DVM was found to be the most suitable level for extension of the ready-to-cook mix. Therefore, extension with dehydrated vegetables could serve to meet technological and functional properties in the development of convenient, nutritious and tasty ready-to-cook dehydrated mix, which could serve an alternative to fresh meat cutlets.